129 Greater NREM Sleep Rebound in Response to Experimental Sleep Disturbance Associated with Higher Inflammatory Resolution in Humans. (3rd May 2021) - Engert, Larissa; Dubourdeau, Marc; Dang, Rammy; Mullington, Janet; Haack, Monika
Abstract: Introduction: Sleep disturbances deteriorate immune function by not only affecting pro-inflammatory pathways, but also inflammatory resolution pathways, which actively terminate inflammation. It is assumed that slow wave sleep (SWS) amount and slow wave activity (SWA) convey the immune-supportive functions of sleep. We investigated whether changes in SWS induced by experimental sleep disturbance followed by recovery sleep predict changes in inflammatory resolution mediators. Methods: The randomized controlled within-subjects trial (N=24, 20-42 years, 12 women) consisted of two 19-day in-hospital protocols (experimental sleep disturbance/control). After three nights of baseline sleep (8h/night), participants in the experimental sleep disturbance condition were exposed to three cycles of three nights of disturbed sleep (delayed sleep-onset, hourly sleep disruption, advanced sleep-offset) followed by one night of 8h-recovery sleep. The protocol ended with three nights of recovery sleep. In the control condition, participants had uninterrupted sleep (8h/night). Sleep (PSG) and resolvin lipid mediators in plasma (1100h, LC-MS/MS) were assessed at baseline, during the last cycle of sleep disturbance, and during/after the first and third night of final recovery sleep. Data were analyzed using generalized linear mixed models and Pearson/Spearman correlations. Results: As expected, SWS amount decreased during experimental sleep disturbance and increased during the first recovery sleep night (p<.001). Similarly, resolvin (Rv) D2 and RvD3 decreased during sleep disturbance and RvD2 increased with subsequent recovery sleep (p<.001). The SWS response did not correlate with the resolvin response to sleep disturbance or to recovery sleep. However, the NREM sleep response correlated with the resolvin response during the third recovery sleep night, i.e., a greater NREM response was associated with a greater RvD2 and RvD3 response (r=.68, p=.002; r=.58, p=.012). In contrast, a greater REM sleep response was associated with a lower resolvin response (r=−.63, p=.005; r=−.66, p=.003). Conclusion: These data suggest that during recovery from sleep disturbance, NREM rather than REM sleep promotes inflammatory resolution, thereby acting as the sleep state that protects against low-grade systemic inflammation, which has been frequently observed as a consequence of sleep disturbances. Analysis whether SWA is related to inflammatory resolution is in progress. Support (if any): NIH/NINDS R01-NS091177; NIH/NCRR UL1-RR02758, M01-RR01032; German Research Foundation (DFG) EN1291/1-1.